Propuesta de un plan estratégico para el Gobierno Autónomo Descentralizado de la parroquia Quiroga período 2012-2016 - Vera Espinoza, José Rodolfo (2013)
Present thesis aimed at 2012-2016 proposing the design of a strategic plan to project the socioeconomic development of his territorial circumscription for the period principally, for which the study came true and evaluation of the present-day situation of this parochial Government, through a collecting system of data that understood polls, interview and a guide of direct observation, to identify problems, to examine the information, to propose the solution and to reflect it in a strategic plan. Besides, they determined the strategic axes that the vestry should focus itself. This investigation sustains itself in real data gathered by the investigators and backed in laws used in investigation. Quiroga's GAD collaborated with the necessary information to know the origin and the reality of this territory. With this base investigation elaborated him the elements keys that form the proposal of the strategic plan, emphasizing that the population should get involved more in public decisive processes. The legal documents countersigned by authority include nominator themselves in order to hold the veracity of investigation and for the postulants of the thesis.